An Online Electrochemical System for Continuously Monitoring Uric Acid Change following Rabbit Kidney following Ischemia-reperfusion Injury. (10th August 2016) - Lin, Yuqing; Li, Bo; Hao, Jie; Xiao, Tongfang; Yang, Yan; Yu, Ping; Mao, Lanqun
Abstract: In vivo monitoring of uric acid (UA) with high reliability and robustness is of great physiological and pathological importance because UA, as one kind of the most important chemical species in the biological systems, plays a great role in some physiological processes and is used as the biomarkers for early diagnosis of several diseases. In this study, a microfluidic chip-based online electrochemical system (OECS) is developed for the first time for continuously monitoring UA in rabbit kidney. To establish the OECS for UA monitoring, a single-channel microfluidic chip is developed into an electrochemical cell by incorporating a single-walled carbon nanotubes (SWNTs)-modified indium-tin oxide (ITO) electrode as working electrode, an Ag/AgCl wire as reference electrode, and a Pt tube as counter electrode. To completely remove ascorbic acid and thus eliminate its interference toward UA detection in such a single-channel microfluidic chip, ascorbate oxidase (AOx) is crosslinked onto both the etched ITO glass in the upstream channel and the SWNT-modified ITO electrode in the downstream. With the as-prepared microfluidic chip-based electrochemical cell as the detector for selective detection of UA, an online electrochemical system is successfully established by directly coupling the microfluidic chip-based electrochemical detector with in vivo microdialysis. The system exhibits a good linear response, high stability and good in vivo selectivity and is thus able to continuously sense UA change in rabbit kidney following ischemia-reperfusion injury. The study essentially offers a new OECS for in vivo continuous monitoring of UA.